Machine bodies, genders, technologies - Hampf, M. Michaela 1971-; Snyder-Körber, MaryAnn (American studies, 2012)
Women’s work. Manning the machine. Bodies electric in an age of the mechanical. Such phrases highlight a crosshatched network of meaning-making in modernity. Technological developments in the concrete sense of devices and operations intersect with longer-standing conceptual architectures. The essay collection ‘Machine: Bodies, Genders, Technologies’ explores key interstices of this evolving techno-cultural imaginary through interdisciplinary dialogue. Literary and historical perspectives within American Studies are brought into conversation with Film, Gender, Media, and Transnational Studies. Contributions consider politics of the body from radical self-fashioning to infections of the body politic, the interrelation of gender and technology from the factory floor to the film screen, and imaginations of the technological between the mechanic and the machinic from nineteenth-century electroshocks to millennial avant-gardes.